ASI plaque at the entrance of the Harshnath Temple Complex - Temples of India Project Team (Jio Institute, 2024)
The plaque reads ‘The temple of Shiva Harshnath, the family deity of Chahamana rulers, situated on the Harsha-giri depicts the Maha-Maru style. According to an inscription dated V.S. 1030 (CE973), it was built by a Shaiva ascetic Bhavarakta, alias Allata, in CE 956 during the reign of Vigraharaja I of the Chahamana dynasty. Chand Shiva was the chief architect. The temple complex consists of garbhagriha, antarala, rangamandapa with kakshasana and porch with a separate Nandi mandapa. Originally, the temple was adorned with a spire. Though now in a ruined condition, it was noteworthy for its architectural landmark and high-quality sculptures of Brahmanical divinities and decorative panels of kirtimukha motifs, dancers and musicians, warriors, etc. Adjoining the main temple is another temple of the late medieval period also dedicated to Shiva, which is built on a very high platform. Besides a Bhairav shrine is also at some distance in the complex.’